ENGLISH FOR SPECIFIC PURPOSES MATERIAL ENRICHMENT: APPLICATION OF STANDARD TRAINING OF CERTIFICATION OF WATCHKEEPING (STCW) YOUTUBE VIDEOS ON CADET’S LISTENING COMPETENCY - Silalahi, Aliong (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Maritime world and industry across the globe employ people from different countries which have a multicultural background. English as the most common second language in the world is really used and important as a language to communicate in the ship. So, English language proficiencies and skills are a must. In order to have common general standards in language (English) for maritime there must be regulation regarding the standardization itself. The requirements for communicative competence of seafarers in STCW present a great challenge to Indonesian seafarers who will struggle to improve their linguistic competences, since in Indonesia English is still known as a foreign language. The research taken place at Merchant Marine Polytechnic of Sulawesi Utara with population of the sample is cadets in Ship Engineering study program. The research aims to evaluate the current Maritime English course curriculum in Indonesian shipping or maritime vocational colleges-universities by analysing communication skills required by seafarers on fishing vessels. Data was gathered from documents and interviews with industry participants. The results indicate that the current exam is inadequate in preparing students for global seafarer standards. The study suggests a genrebased approach for English language courses, including Maritime English (ESP), to enhance cross-cultural knowledge and improve work skills. This approach can help university graduates gain a competitive edge in the labor market by improving communication and work performance.